2011
DOI: 10.1128/jb.00369-11
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage Inactivates the Staphylococcus aureus Lipoteichoic Acid Synthase

Abstract: Lipoteichoic acid (LTA) is a crucial cell envelope component in Gram-positive bacteria. In Staphylococcus aureus, the polyglycerolphosphate LTA molecule is synthesized by LtaS, a membrane-embedded enzyme with five N-terminal transmembrane helices (5TM domain) that are connected via a linker region to the C-terminal extracellular enzymatic domain (eLtaS). The LtaS enzyme is processed during bacterial growth, and the eLtaS domain is released from the bacterial membrane. Here we provide experimental evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 47 publications
5
100
0
Order By: Relevance
“…LtaS is a polyglycerol phosphate synthase involved in the synthesis of lipoteichoic acid, which is a component of the S. aureus envelope (33,34). It was recently demonstrated that SPase processes LtaS in S. aureus (115), which our results confirm, and along with our previous demonstration that SPase processes LtaS in S. epidermidis (82) suggests that SPase-mediated cleavage of LtaS is general and possibly physiologically significant. OatA is an O-acetyltransferase and an integral membrane protein that confers the high level of resistance to lysozyme observed in the staphylococci by O-acylating peptidoglycan muramic acid (13).…”
Section: Discussionsupporting
confidence: 81%
“…LtaS is a polyglycerol phosphate synthase involved in the synthesis of lipoteichoic acid, which is a component of the S. aureus envelope (33,34). It was recently demonstrated that SPase processes LtaS in S. aureus (115), which our results confirm, and along with our previous demonstration that SPase processes LtaS in S. epidermidis (82) suggests that SPase-mediated cleavage of LtaS is general and possibly physiologically significant. OatA is an O-acetyltransferase and an integral membrane protein that confers the high level of resistance to lysozyme observed in the staphylococci by O-acylating peptidoglycan muramic acid (13).…”
Section: Discussionsupporting
confidence: 81%
“…1A and B). This processing site has been confirmed for LtaS SA (39,44), and a similar processing is observed for the LtaS enzymes of B. anthracis (see below).…”
Section: Resultsmentioning
confidence: 59%
“…Bursa aurealis transposon mutants from the Nebraska Library were obtained from the Network on Antimicrobial Resistance in Staphylococcus aureus (NARSA). The LAC ⌬aur ⌬sspAB ⌬scpA ⌬spl::Er (protease-null) mutant was provided by Lindsey Shaw (University of South Florida, Tampa, FL) (35). The LAC and COL sarA::Km r mutants were generated by 11-mediated transduction from a previously constructed mutant (36).…”
Section: Methodsmentioning
confidence: 99%